2008
DOI: 10.1002/hec.1416
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the monetary value of a QALY: a new approach based on UK data

Abstract: Debate about the monetary value of a quality-adjusted life year (QALY) has existed in the health economics literature for some time. More recently, concern about such a value has arisen in UK health policy. This paper reports on an attempt to 'model' a willingness-to-pay-based value of a QALY from the existing value of preventing a statistical fatality (VPF) currently used in UK public sector decision making. Two methods of deriving the value of a QALY from the existing UK VPF are outlined: one conventional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
107
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 21 publications
3
107
0
Order By: Relevance
“…To value QALYs in monetary terms, the social value of a quality adjusted life year can be used-work on valuing QALYs is less developed than that for valuing statistical lives, but some estimates do exist. For example, Mason et al (2009) compare the value for life years and the value of QALYs and find that the QALYs may be worth between £34,925 and £70,896 and life years £29,691-£57,569.…”
Section: Mortalitymentioning
confidence: 99%
“…To value QALYs in monetary terms, the social value of a quality adjusted life year can be used-work on valuing QALYs is less developed than that for valuing statistical lives, but some estimates do exist. For example, Mason et al (2009) compare the value for life years and the value of QALYs and find that the QALYs may be worth between £34,925 and £70,896 and life years £29,691-£57,569.…”
Section: Mortalitymentioning
confidence: 99%
“…This is an area of research in its own right. Applying the method of estimating the WTP based on the existing value of preventing a statistical fatality, Mason et al suggested that the WTP for a discounted QALY was nearly £69,000 (without adjustments) and £31,000 (with age adjustment, apply for young adults) [75]. Using the same technique but in Swedish population, Johannesson and Meltzer estimated a WTP per QALY gained of around US $90,000 [28].…”
Section: Citationmentioning
confidence: 99%
“…Revealed preference or contingent valuation (stated preferences) studies (97,(290)(291)(292) have been used to directly elicit the monetised value of a QALY. Revealed preference studies are based on real world market transactions that represent actual risk-taking behaviours (97, 293).…”
Section: Conversely Others (Johannesson and Jönssonmentioning
confidence: 99%
“…In welfare economics such utility value represents the societal willingness to pay to benefit from an intervention's outcome (97). Hence, for CBAs of health related initiatives, methods are needed to elicit a monetary value as a measure of what society is willing to sacrifice in order to gain an improvement in health.To date, the literature presents the monetary value of a quality-adjusted life year (QALY), which like our estimated HALYs represents the length and quality of life (97,(290)(291)(292). Another population health measure that represents length and quality of life is the disability-adjusted life year (DALY).…”
mentioning
confidence: 99%
See 1 more Smart Citation